183 Improving Documentation of Antibiotic Prophylaxis and Anticoagulation in Vascular Surgery Operation Notes at a Tertiary Centre: A Quality Improvement Project. (19th August 2022) - Curlewis, K; Weerakkody, R; Harris, M; Constantinou, J
Abstract: Aim: Operation notes have important medico-legal implications and should follow the Good Surgical Practice framework to enable continuity of care. The aim of this quality improvement project was to determine adherence of vascular surgery operation notes to the Good Surgical Practice framework at a tertiary vascular centre, identify areas of improvement and introduce sustainable change to improve patient care. Method: Two Plan-Do-Study-Act cycles were enacted. A prospective audit was conducted over September 2021 to identify areas of improvement in documentation. The first intervention that was introduced was electronic patient records (EPR). The second intervention introduced was departmental education via posters, regular educational sessions, and presentations. Results: The prospective audit of 31 operations over September 2021 identified antibiotic prophylaxis was only recorded in 4/31 (13%) and post-operative anticoagulation in 21/31 (68%). A retrospective audit of 28 operations over October 2021 after the introduction of EPR demonstrated improved documentation of antibiotic prophylaxis (16/28, 57%) but no improvement in post-operative anticoagulation documentation (17/28, 61%). Departmental education improved the documentation of antibiotic prophylaxis (18/30, 60%) and post-operative anticoagulation (22/30, 73%). Conclusions: We have demonstrated that EPR and departmental education can improve operation note documentation and patient care. Next steps include designing vascular surgery proformas to further improve documentation.